AN ANALYSIS OF WORD FORMATION IN LOCAL AND INTERNATIONAL COSMETIC BRANDS - Rizki Nanda Safira; Ferry Kurniawan (Jotika English and Education Center, 2022)
This study is entitled An Analysis Of Word Formation In Local And International Cosmetic Brands. In this study, the researcher analyzed the word formation processes of 25 local and international cosmetic brands on Shopee. There were two purposes of conducting this research. (1) To classify and find the categories of word formation in local and international cosmetic brands on Shopee, (2) To find out the patterns and meanings in local and international cosmetic brands. In this study, the researcher did the qualitative research with descriptive approach. For the technique of collecting the data, the researcher used documentation study technique. The researcher used the theory of word formation by Yule (2010). For the result the researcher found 5 categories of word formation processes in 25 local and international cosmetic brands. They were 6 items for borrowing, 6 items for compounding, 4 items for blending, 6 items for acronyms and 3 items for multiple processes.